COSPLAY AS RECREATIONAL AND TOURIST EVENT IN UKRAINE - Артеменко, М. П. (Art and Design, 2019)
The purpose of the study is to identify the characteristics of the development of the cosplay in Ukraine as a recreational and tourist event, the concept of which is based on the creation by participants of images of popular heroes using a costume. The research methodology is based on a critical analysis of publications, quantitative and qualitative processing of the facts of conducting events with a cosplay in Ukraine revealed by the author, statistical and graphic methods of data processing. Results. The article presents the results of a study of the development of cosplay in Ukraine, which reveal the trend of growth of its popularity, which has a wave-like nature with peaks of activity in even years. This fact is explained by the holding of some events in the biennial format. It is noted that in most regions of Ukraine the facts of conducting competitions or parades of costumes, which are reproduced images of popular cartoon characters, cinema, comic books, computer games or literature, have already been recorded. Accordingly, Ukraine has a sufficient number of supporters of the cosplay to consider it as a means of recreation and a tourist resource, the concept of which is based on the use of the costume when participants create an image of a popular hero. The organization of such events is proposed to be considered a factor in stimulating internal and external tourist flows, as well as on of a new direction for the fashion industry in Ukraine in designing and manufacturing clothing for thematic cultural events. Scientific novelty. For the first time, the features of the development of a cosplay in Ukraine were identified, trends in the popularity of this cultural phenomenon and the localization of major festivals were identified, which is the basis for the further development of recommendations for designing artistic images and costumes for participants in thematic recreational and tourist activities. Practical significance. The results reveal opportunities for a deeper understanding of the role of costume in the modern list of recreational and tourist activities, and can also be used in the training of design and art historians as a basis for analyzing the history of the development of subcultures, as well as in the practice of designers, costume artists, managers on tourism and others.